Informacinių įgūdžių ugdymas Lietuvoje - Vladimirovas, Levas; Dagytė, Ina; Kancleris, Algirdas (Knygotyra, 1974)
The developing of informational habits and skills has in Lithuania its deeplyrooted historic traditions (the pioneers in this field at the beginnig of the 19th century were G. E. Groddeck, A. Bohatkiewicz, J. Lelewel etc.). Nowadays under the existing favourable conditions of the scientific-technical revolution there has matured the pressing necessity to create a system for developing of informational habits and skills covering the educational (secondary and higher education) and post-educational periods.The Chair of Scientific Information of the Vilnius V. Kapsukas State University has worked out a number of measures to develop informational habits during the educational period: A differentiated basic course of „Information science“ for secondary special schools and schools of higher education of the Lithuanian republic has been prepared, a number of teaching appliances has been published, in the years 1971 and 1972 a series of educational lectures through television has been organized.The analysis of the results of all these measures gives (in the opinion of specialists and students) the right to assert that our system of developing informational skills and habits is useful and effective.